Survival and growth of Pangasianodon hypophthalmus cultured under controlled photoperiod - Cyntia Uli Artha Sihombing; Muhammad Fauzi; Windarti Windarti (Depik, 2021)
Changing in photoperiod duration may affects the physiology of nocturnal fish such as Pangasianodon hypophthalmus. A study aims to understand the effects of controlled photoperiod towards survival and growth of P. hypophthalmus has been conducted from June to August 2020. There were 3 treatments applied, namely natural photoperiod, 18 hours dark (18D), and 24 hours dark (24D) with 3 replications in each treatment. The rearing tanks used in this study were 100 L circular plastic tanks. In 24D treatment, the tanks were placed under dark colored tarp tent continuously. For the 18D treatment, the tanks were placed under dark tarp tent, but the tent was opened for 6 hours/ day (the tanks were in dark condition for 18 hours/ day), while the control tanks were positioned under natural photoperiod. P. hypophthalmus fingerlings, 6-8 cm TL and 4-5 g BW were used in this study. Thirty fishes were reared in each rearing tank, they were feed with commercial pellets, 2 times/day, at satiation. Fish survival was monitored every day, while samplings for fish growth were conducted weekly for a 8 weeks period. Results indicate that the survival of fish was 100% in each treatment applied. Fish growth, however, shown differences. The growth of fish reared in 24D and 18D was better than that of the control. By the 9th week, the fish in 24D was around 70.71g BW with 19.27 cm TL (daily growth rate 9.35%), while those of the 18D was 69.41 g BW, 18.77 cm TL and 9.29% daily growth rate. The fish reared under natural photoperiod was around 61.95 g BW with 18.19 cm TL and 7.33% of daily growth rate. Data obtained indicate that the application of longer dark is positively improve the growth of P. hypophthalmus.Keywords:Nocturnal FishLight Dark Catfish